The Influence of Motivation, Entrepreneurship, and Utilization of Information Technology of Management on the Performance of KPRI Cooperatives in Bangkalan Regency - Manah Tarman; Ika Lis Mariatun (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines whether work motivation, entrepreneurial orientation, and information technology (IT) utilization are associated with the performance of Republic of Indonesia Employee Cooperatives (Koperasi Pegawai Republik Indonesia, KPRI) in Bangkalan Regency. Design/methodology/approach – A quantitative, cross-sectional explanatory survey was conducted in May 2025. Questionnaire responses were obtained from 106 KPRI administrators representing 36 cooperatives and analyzed using descriptive statistics, item-total correlations, Cronbach's alpha, diagnostic tests, and multiple linear regression. Finding/Results – The regression model was statistically significant, F(3, 102) = 18.551, p < .001, and explained 35.3% of the variance in cooperative performance (adjusted R² = .334). Work motivation had a positive unique association with performance (B = .341, beta = .286, p = .009). Entrepreneurial orientation (B = .151, beta = .218, p = .055) and IT utilization (B = .151, beta = .187, p = .072) were positive but did not reach the conventional .05 threshold after adjustment for the other predictors. Originality/Value – By testing motivational, entrepreneurial, and digital factors in a single model within Indonesian employee cooperatives, the study shows that collectively relevant capabilities do not necessarily make equally strong unique statistical contributions. The findings refine performance priorities for locally embedded cooperatives and caution against interpreting digital adoption or entrepreneurial orientation as automatic performance gains.